Pemanfaatan Limbah Peternakan: Pelatihan Pembuatan Pupuk Kompos di Desa Sidomulyo Kecamatan Salaman - Ngatiyem, Ngatiyem; Romzah, Romzah; Sari, Siti Sarmeiliya; Dewanto, Sindu Adi; Imani, Restu Teguh; Wafiqah, Naufal Chasna; Afanti, Yasinta Laila; Aulia, Yuniar Cindi; Rosadi, Imron; Ohorella, Raja Putra Ramadhan (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
Livestock and agricultural activities produce continuous waste, socialization and training activities on making compost based on livestock and agricultural by-products are carried out as an effort to reduce waste production in the hope that community understanding of waste utilization can increase and can help the economy. The socialization activity of making compost organic fertilizer in Dusun Sojomerto Kidul, Desa Sidomulyo, Kecamatan Salaman, Kabupaten Magelang and continued with the practice of making compost fertilizer made from cow feces and rice straw. The activity went well and the community was enthusiastic in participating in every activity. This socialization was able to provide valuable knowledge and knowledge for the community, adding insight into compost fertilizer and how to make it.